MetroSonus. An inclusive alternative for the training and direction of visually impaired musicians - Gaitán Lozano, Diego Felipe; Reina Zambrano, Juanita (Revista Electrónica Complutense de Investigación en Educación Musical - RECIEM, 2024)
MetroSonus arises as a result of an investigation that aims to create a proposal for the development of a technological tool that tends to the inclusion of people with visual disabilities in musical training spaces, either as an apprentice, as a musician part of an ensemble or as a counselor or director. This pedagogical tool transmits the pulse of the conductor to networked mobile devices, in order to support the teaching-learning processes, as well as music interpretation.The methodological orientation of this project is supported, from the qualitative approach, in the Praxeological Research proposal developed by UNIMINUTO, which has as its axis the reflection on the practice and at the same time delimits the research process in four moments: See, Judge, Act, and Creative Return.This research project poses new challenges and training demands in the various areas, which were explored for the development of metroSonus, as well as in the field of inclusive education and in those that are necessary to give continuity to this project, such as computer vision, machine learning and artificial intelligence.
Keywords: music; inclusion; blindness; visual impairment; technology; web application